2020
DOI: 10.3390/jcm9040957
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Impact of Hexanic Extract of Serenoa repens in Men with Prostatic Inflammation: A Post Hoc Analysis of a Randomized Biopsy Study

Abstract: A randomized biopsy study showed that hexanic Serenoa repens (HESr) treatment resulted in prostatic inflammation reduction. This post-hoc analysis evaluated the clinical impact of HESr and investigated correlations between baseline parameters and treatment response. Patients were randomized to receive HESr 320mg/day for six months or no therapy. Assessment included International Prostate Symptoms Score (IPSS), prostate volume (PV), and maximum flow rate (Qmax). Baseline characteristics were recorded, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…After six months of follow-up, patients receiving the HESr reported better outcomes in terms of symptoms and QoL than patients managed with watchful waiting. The focus on QoL in the present study and the inclusion of patients with moderate-severe symptoms adds to evidence from earlier studies which studied the effects of the HESr in patients with mild symptoms [20], or reported the effect on clinical symptoms, rather than QoL [21,22], or which focused on the HESr's anti-inflammatory action [23].…”
Section: Discussionmentioning
confidence: 82%
“…After six months of follow-up, patients receiving the HESr reported better outcomes in terms of symptoms and QoL than patients managed with watchful waiting. The focus on QoL in the present study and the inclusion of patients with moderate-severe symptoms adds to evidence from earlier studies which studied the effects of the HESr in patients with mild symptoms [20], or reported the effect on clinical symptoms, rather than QoL [21,22], or which focused on the HESr's anti-inflammatory action [23].…”
Section: Discussionmentioning
confidence: 82%
“…The key drivers of HESr combination therapy choice were reported as clinical symptom alleviation, strong association with the lack of sexual dysfunction risk and reduction of inflammation [ 50 ]. In addition, patients with PIS and a specific clinical profile tend to show a better treatment response and should be targeted for combination treatment [ 37 ]. The general clinical condition and comorbidities of the patient should be carefully evaluated in order to personalise the treatment and choose the right therapy for the right patient.…”
Section: Discussionmentioning
confidence: 99%
“…HESr has been shown to have anti-inflammatory, anti-androgenic and anti-proliferative activity [ 33 , 34 , 35 ]. Recent studies have demonstrated that HESr relieves LUTS by reducing underlying prostatic inflammation [ 12 , 36 , 37 ]. In a randomised clinical trial including 97 patients with histologically confirmed prostatic inflammation on prostate biopsy, 6 months of treatment with HESr (320 mg/day) significantly improved Irani’s inflammation grading, aggressiveness and total score in a second prostate biopsy done after the treatment ( Figure 2 ) [ 36 ].…”
Section: Overview Of Hesr Monotherapy In the Management Of Luts/bphmentioning
confidence: 99%
See 2 more Smart Citations